We're still here [videorecording (DVD)]. (Films Media Group, Film for the Humaniites & Sciences, 2020)
First Nation indigenous hip hop artists in Canada lead efforts to right long-standing social injustices, heal personal traumas, and preserve their cultures through the power of music. The film examines the important role that hip hop plays in transforming the lives of the musicians, their audiences, and communities. Weaving together interviews, live performances, and street demonstrations, it gives voice also to other marginalized populations across North America.